Prediksi Bobot dan Konformasi Karkas Kambing Lokal Mengunakan Prediktor Bobot Potong dengan Berbagai Model Regresi - Akhmad Sodiq (Jurnal Agripet, 2011)
Prediction for carcass weight and conformation of local goat by slaughter weight predictor using some regression modelsABSTRACT. The goat population of Indonesia is concentrated in Central Java province especially under smallholder farming areas, and mostly their function is the production of meat. Local breed (Jawa Randu and Peranakan Etawah Crossbred) are very common raised by samallholders in Banyumas areas. The local kids are raised with their mothers and slaughtered after post weaning (68 months old). Carcass characteristics are important criteria for consumers and it could be taking into account. The objective of this study was to estimate the carcass weight and conformation of local goat by predictor of slaughter weight using some regression models. Eighty male of local goats (Peranakan Etawah and Jawa Randu crossbred), body weight ranged from 10-23.5 kg (6-8 months of age) resulted from village production system were used in this study. Carcass weight, dressing percentage, and carcass conformation were recorded. Ten models of estimation curve procedure were applied in terms of linear and nonlinear regression models. The analysis display relation between slaughter weight (X) and carcass weight and conformation (Y). The higher of determination coefficient (r2) and the lowest of the standard error means (M.SE) was found in the power regression model. Carcass weight of local goat (Y) could be effectively assessed by slaughter weight (X) using power regression model Y= 0.593907 (X 0,893021 ) or ln (Y) = ln (0.593907) + 0,893021 ln(X); and conformation carcass (Y) could be effectively predicted by slaughter weight (X) using power regression model Y= 14.995466 (X 0,267867 ) or ln (Y) = ln (14.995466) + 0,267867 ln (X).